Electromagnetics Vol 1 - Ellingson, Steven W.; Open Textbook Library (Open Textbook Library, 2018)
Electromagnetics Volume 1 by Steven W. Ellingson is a 238-page, peer-reviewed open educational resource intended for electrical engineering students in the third year of a bachelor of science degree program. It is intended as a primary textbook for a one-semester first course in undergraduate engineering electromagnetics. The book employs the "transmission lines first" approach in which transmission lines are introduced using a lumped-element equivalent circuit model for a differential length of transmission line, leading to one-dimensional wage equations for voltage and current. Additional ResourcesProblem sets and the corresponding solution manual are also available.
Chapter 1: Preliminary Concepts -- Chapter 2: Electric and Magnetic Fields -- Chapter 3: Transmission Lines -- Chapter 4: Vector Analysis -- Chapter 5: Electrostatics -- Chapter 6: Steady Current and Conductivity -- Chapter 7: Magnetostatics -- Chapter 8: Time-Varying Fields -- Chapter 9: Plane Waves in Lossless Media -- Appendix A: Constitutive Parameters of Some Common Materials -- Appendix B: Mathematical Formulas -- Appendix C: Physical Constants
In English.
Description based on print resource
Keywords: Engineering -- Textbooks; Physics -- Textbooks; Electrical Engineering -- Textbooks